The resting place - Sten, Camilla, 1992- (Minotaur Books, 2022)
Inheriting a house tucked away in the Swedish woods from her cruel grandmother, Eleanor, seeking the truth about her grandmother's murder and the killer, soon regrets disturbing what rests in this place with a dark past.